Effect of Static Magnetic Field Assisted Thawing on Physicochemical Quality and Microstructure of Frozen Beef Tenderloin - Jiang, Junbo; Zhang, Liyuan; Yao, Jianbo; Cheng, Yue; Chen, Zhongrong; Zhao, Gang (Frontiers in Nutrition, 2022)
Although freezing is the most common and widespread way to preserve food for a long time, the accumulation of microstructural damage caused by ice crystal formation during freezing and recrystallization phenomena during thawing tends to degrade the quality of the product. Thus, the side effects of the above processes should be avoided as much as possible. To evaluate the effect of different magnetic field strength assisted thawing (MAT) on beef quality, the indicators associated with quality of MAT-treated (10 to 50 Gs) samples and samples thawed without an external magnetic field were compared. Results indicated that the thawing time was reduced by 21.5-40% after applying MAT. Meat quality results demonstrated that at appropriate magnetic field strengths thawing loss, TBARS values, cooking loss, and shear force were significantly decreased. Moreover, by protecting the microstructure of the muscle, MAT significantly increased the a* value and protein content. MAT treatment significantly improved the thawing efficiency and quality of frozen beef, indicating its promising application in frozen meat thawing.